An Intervention Study: Does a Cognitive Reappraisal Technique Reduce the Perceived Stress in Fourth-Year Dental Students in New Zealand? - Alana Smith; Imogen Scott; Jithendra Ratnayake; Kate Newsham-West; Peter Cathro (International Journal of Dentistry)
Background. The fourth-year of the Bachelor of Dental Surgery (BDS) degree is considered the most stressful in the curriculum. Cognitive reappraisal is a self-applied method of stress management where an individual recognises his/her physiological responses to stress as a positive phenomenon helping him/her rise to the challenge, rather than a negative one in response to a threat situation. Aim. To investigate whether teaching fourth-year dental students to apply cognitive reappraisal reduces their perceived levels of stress. Methods. A survey was emailed to all fourth-year dental students, inviting them to respond to a 20-item questionnaire adapted from the Dental Environmental Stress (DES) Survey. Respondents were randomly assigned to reappraisal intervention/experimental (EXP) and control intervention (CON) groups, and each group was asked to watch an educational video. The EXP group video educated respondents on how to apply cognitive reappraisal in stressful situations, and the CON group video described generic methods of stress management. A follow-up survey was conducted after 3 weeks. Results. The respondent rate was 47.6%. Change scores were calculated by subtracting the follow-up DES scores from baseline DES scores. The average change score for the experimental group was +3.1, indicating a decrease in average perceived stress levels. Conversely, the average change score for the CON group was −1.06, indicating an increase in average perceived stress levels. However, this difference did not reach a statistical significance. Conclusion. EXP group has shown to have positive effects on stress management, and its effects on BDS students demonstrate promise.